Anterior tooth trauma among schoolchildren aged 10-19 years in Mewat district, India - Amita Sharma; Sarika Sharma; Sonam Sharma; Rachit Sharma (Wolters Kluwer Medknow Publications, 2021)
Background: Dental trauma is relatively common, with its incidence and prevalence varying not only within countries and states but also within different socioeconomic groups. A primary goal in oral health care is to prevent dental trauma. Objectives: The aim of the present study was to determine the prevalence of anterior tooth trauma (ATT) and to analyze factors associated with ATT among schoolchildren aged 10-19 years in Mewat district, an underdeveloped and underprivileged area in Haryana state, India. Methods: A cross-sectional study was conducted among 3043 schoolchildren residing in Mewat district. They were divided into the following age groups: 10-13, 14-16, and 17-19 years. Dental injuries to anterior teeth were recorded according to Ellis and Davey's classification. Data were collected using a specifically designed questionnaire. The data were analyzed using IBM Statistical Package for Social Sciences for Windows (version 20.0). Categorical variables are presented as proportions (%), and Pearson's χ2 test was used to analyze these variables. Tests were conducted at the significance level of 5%. Results: Of the 3043 schoolchildren (males, n = 2178; females, n = 865) examined in the study, 362 schoolchildren had experienced dental trauma, giving a prevalence rate of 11.89%. Males were more prone to ATT (13.36%), and an Ellis Class I fracture was the most frequent type of ATT (78%). The most common causes of ATT were falls (49.44%), followed by road traffic accidents. In addition, children with partial lip coverage and an overjet of more than 3 mm had an increased risk of ATT. Conclusion: The prevalence of ATT among schoolchildren in Mewat district was 11.89%, and the major etiological factor was a fall. There is an increased need for awareness of dental trauma in school-aged children.